O Amanuense Belmiro, Fogo Morto e São Bernardo: formas do trágico no capitalismo tardio - Barbara Del Rio Araujo (2018)
On a general panorama of the 1930 novel production, it´s possible to note the narratives show a pungent disbelief in the country transformation possibility and have a maturated perspective about the delay and national decadence. On this way, renowned critics as João Lafetá, Antonio, Candido and Luiz Bueno perceive on the period books a disaggregation of the utopic modernist mentality, which face Brazil as a new country, and the instauration of a pre-conscious of underdevelopment and the insistent survival from the archaic elements of Brazilian society. Then, Cyro dos Anjos, José Lins do Rego, Graciliano Ramos and others writers were able to stylize, which one by its preference, resorting the intimacy and regional aspects, the familiarity between progress and retard, imbuing its plots with the tragic aspect. This research aspire to show representations of this contradictory progress, by the O amanuense Belmiro, Fogo Morto and São Bernardo analyses, reveling the tragic concentrated in the destiny and crises from human figure, which becomes depositary of conflicts and mantises from the Brazilian reality, which develops in unequal way, but combined. Then, the tragic action on these narratives does not revel as a simple prolongation from the classic tragedy, there is a different representation, which presuppose and interpret the part of common and quotidian life. Refers to a modern conception, the tragic here approached represents a permanent contradiction between the matter and the spirit, the affirmation and, on the same time, the annihilation of the individual in front of the world. Adhering to the novel, the tragic element becomes to be analyzed in consonance with the history, part of its particular construction, configuring series of private manifestations about its time as the conflict the human and its historical-social conjuncture. It is not a goal from this study the syntheses about the tragic historic evolution, but aims to comprehend the manner O amanuense Belmiro, Fogo Morto and São Bernardo use the tragic as articulator of the formal aesthetic composition and the literary demands from the 30 and 45 decays, performing the representation of decadence as the literary critic named. Ahead this reasoning line, we intend to observe how the tragic phenomenon acts as a dispositive that allows the elaboration of a vision about the Brazilian modernity and operate an interpretation movement between the social and aesthetics aspects, becoming, so, indispensable to understand the writings from the period.